High-density radio-frequency magnetized plasma sputtering source with rotational square-shaped arrangement of rod magnets for uniform target utilization. (June 2016) - Hossain, Md. Amzad; Ide, T.; Ikari, K.; Ohtsu, Y.
Abstract: We have developed a high-density radio frequency (RF) magnetized sputtering plasma source with a rotational square-shaped magnet arrangement for uniform target utilization. Eight neodymium rod magnets of 30 × 5 × 3 mm, where the connection between N-pole and S-pole magnets is one side of the square, are mounted on a circular iron yoke disc and an iron cover of 5 × 3 × 1 mm is also used for magnetic shielding of otiose magnetic fields from the permanent magnets. The magnetic field simulation, the measurement of the target erosion and the time-averaged ion flux to the target have been investigated (a) without iron cover and no air gap between N-pole and S-pole magnets, (b) with iron cover and no air gap, and (c) with iron cover and 5 mm air gap, respectively. It is found that the iron covers suppress the horizontal magnetic flux density and the copper target utilization percentage increases from 74.15% to 87.49%. Moreover, by decreasing the air gap between the shielded magnets, the copper target utilization percentage rises from 83.85% to 87.49%. The target utilization as well as the time-averaged ion flux to the target is optimum for case (b). Highlights: RF plasma sputtering with rotational square-shaped setup of magnets is developed. Plasma emission is observed so as to reflect magnetic field distribution. Magnetic shielding material suppresses needless magnetic field for uniform erosion. Copper target utilization percentage attains 87.49% with magnetic shielding material. High plasma density with more than 10 10  cm −3 is achieved at the center of the target.